2012
DOI: 10.1590/s1020-49892012000100010
|View full text |Cite
|
Sign up to set email alerts
|

Asociación entre la ingesta de nutrientes hematopoyéticos y el origen nutricional de la anemia en mujeres en edad fértil en Colombia

Abstract: Non-hypoferric anemia was most common, with no difference by sociodemographic indicators except in the Pacific region. All the women were at high risk of deficiency in their customary hematopoietic nutrient intake, but a statistically significant association between the deficiency and the origin of the nutritional anemia was not observed. Programs to improve nutrient intake and a continued search for causes of nutritional anemia other than iron deficiency are justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…Currently, no studies that have included this biomarker have been done in Colombian women, nor is there information on risk of deficiency due to dietary intake in WRA. A study done by Manjarrés et al found that 90% of Colombian women with anemia also showed risk of B 6 deficiency (Manjarrés et al, ). We did not find other studies indicating possible associations between supplement intake and vitamin B 6 , however, given that adequate metabolism of homocysteine requires co‐enzyme B 6 , this finding could be important in reserving folate for the conversion of homocysteine to methionine (Gropper et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, no studies that have included this biomarker have been done in Colombian women, nor is there information on risk of deficiency due to dietary intake in WRA. A study done by Manjarrés et al found that 90% of Colombian women with anemia also showed risk of B 6 deficiency (Manjarrés et al, ). We did not find other studies indicating possible associations between supplement intake and vitamin B 6 , however, given that adequate metabolism of homocysteine requires co‐enzyme B 6 , this finding could be important in reserving folate for the conversion of homocysteine to methionine (Gropper et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…During this phase of the life cycle dietary iron deficiency is the main source of risk leading to anemia, although there are other causes, such as infectious diseases and nutritional deficiencies, such as, in vitamin A, vitamin B 12 and folic acid [8][9][10][11] , in other words, it is a nutritional disorder of multifactorial origin 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Dentro de la frecuencia de anemia encontrada en la población de mujeres estudiada, el 5% de ellas presentó anemia ferropénica, correspondiendo al 33,3% de los casos de anemia encontrados; similar porcentaje se obtuvo en un estudio realizado en Colombia, donde del total de casos de anemia observados, el 32,8% correspondió a la ferropénica (24), pero fue inferior al 50% estimado por la OMS (1). Estas diferencias se podrían deber a la diferencia entre las características de las poblaciones analizadas relacionadas con los hábitos alimentarios (4).…”
Section: Discussionunclassified